The Necessity of Mutual Benevolence and Supervision between People and Government and among Members of the Society - hossein izadi (توسعه اجتماعی, 2018)
This article discusses the bases of the eighth principle of the costitution which gets into the mutual responsibilites of government and people toward each other and among members of the society. It also studies the relationship between this principle and "Enjoying the good and forbiding the evil". Disscussing a scientific matter, the prerequisits and assumptions of that matter should be considered and followed in order to come to a clear conclustion. While studying jurisprudence and law bases of enjoining the good and forbiding the evil, they should also be traced in Quran and the Sunnah and in the other two inferential sources, i.e wisdom and consensus. Within the limits of a few pages and not as a book or an extensive research proposal, this article tries to study the value of "Enjoinin the good and forbiding the evil" and its significent social place in holy Quran. If it werenot necessary to state the rules of these two duties in the Sunnah, their Quranic correspondents would adequately satisfy and convince any honest researcher. While the main focus of this article is on the 8th principle of the constitution of Islamic republic of Iran, it has tried to explain all the related issues in Hadith and the Sunnah. The article has concluded that there are enough confirmatory documents to prove the necessity of this benevolent act and its constructive effects on the society and government.